«The creative turn» in European social theory - Matsevich-Dukhan, Iryna Ja. (Journal of the Belarusian State University. Sociology, 2021)
The article reveals specific features of contemporary European social theory within its turn to the nature of creative practices. Different socio-philosophical methods of their cognition are demonstrated. The explication of the character of European social theory as a whole outlines the increasing interest in the formation of a theory of creative society which critically grounds the set of political programmes «Creative Europe». The author defines the concept of the creative turn within a comparative analysis of those theories of contemporary society which explore the peculiarity of social reality constituting on the basis of creative economy. Its practices become a special subject matter of social theory revealing societal limitations of their fulfillment.
Keywords: social theory; European social theory; creative practices; social practices; creative turn; practical turn; creative society; theory of creative society